Age-Related to Breast Cancer Incidence in Cut Meutia General Hospital, Northern Aceh - Adi Rizka; Teuku Yudhi Iqbal; M, Arfini Mertia (Open Access Indonesian Journal of Medical Reviews, 2022)
The risk of breast cancer increases with age, due to the progressive accumulation of genetic and epigenetic changes in breast epithelial cells as well as epigenetic changes in the microenvironment that lead to changes in gene expression. This study aims to determine the relationship between age risk factors and the incidence of breast cancer in Cut Meutia General Hospital, Northern Aceh. The research method used a cross sectional design which was carried out from June 2021 to January 2022. A total sample of 52 breast cancer patients were taken by total sampling that met the inclusion criteria. We found that patients with the most age characteristics are in the 41-50 age group with elementary education level, living in Aceh Utara and housewives. Based on the stage, it is known that the most dominant stage of the patient experiencing the incidence of breast cancer is stage III, which consist of 25 patients. Also, there is a significant relationship between age risk factors and the incidence of breast cancer in breast cancer patients in Cut Meutia General Hospital, Northern Aceh.